Assessment of Information Needs of Dairy Farmers about Dairy Farming in Karnataka - Shivalika,; Rathod, Prakashkumar; Anjali,; Biradar, Channappagouda (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to determine the information needs of dairy farmers about dairy farming with a sample size of 200  respondents from Karnataka. Purposive and random sampling method was adopted. The statistical techniques used were frequency,  percentage, weighted mean score, ranking, index value, mean index value and independent student t test. The study revealed that  there was a significant difference (p
Keywords: Dairy farmers; Information needs; Karnataka; Livestock productivity